Representando la experiencia. Imágenes e imaginarios en el Imperio español del siglo XVII - Polo y La Borda, Adolfo (Anuario de Historia de América Latina, 2020)
Based on the analysis of the portraits of Pedro Ordóñez de Cevallos and Juan Francisco Montemayor de Cuenca, this article studies the ways in which these two Spanish imperial officials thought, synthesized, and visually expressed their experiences of service to the Spanish king throughout the Spanish Empire. These two cases exemplify very well the life and deeds of many other hundreds of Spanish officials, who during the 17th century travelled around the world building the Spanish Empire, imposing the king´s authority, and preaching Catholicism. In the graphic representations of these officials, as well as of their activities, it is possible to glimpse some of the ideals of the archetype of the royal servant and of the monarchy itself that circulated around the Spanish Empire, giving it cohesion and coherence despite its global and far-flung nature.